2019
DOI: 10.1371/journal.pone.0220852
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey of hospital-based thalassemia patients and standards of care and a preliminary assessment of the national prevention program in Sri Lanka

Abstract: Objectives Our aim was to describe the numbers and distribution of patients with different types of thalassemia and to assess the standards of care in all thalassemia treatment centers throughout Sri Lanka and the success of the ongoing prevention programme. Methods This cross-sectional island-wide survey was conducted by two trained medical graduates, who visited each thalassemia center to collect data from every patient, using a standardized form. Data was collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…One important limitation of our study is that we are unable to generalise the finding of this study to all centres caring for patients with thalassaemia in Sri Lanka. We previously showed that the care provided by larger specialised thalassaemia centres is better than the care provided by smaller centres in the country [9]. Therefore, it is likely that the psychological morbidity of children taking treatment from smaller thalassaemia centres is worse than what is described here.…”
Section: Clinical Characteristicsmentioning
confidence: 49%
See 2 more Smart Citations
“…One important limitation of our study is that we are unable to generalise the finding of this study to all centres caring for patients with thalassaemia in Sri Lanka. We previously showed that the care provided by larger specialised thalassaemia centres is better than the care provided by smaller centres in the country [9]. Therefore, it is likely that the psychological morbidity of children taking treatment from smaller thalassaemia centres is worse than what is described here.…”
Section: Clinical Characteristicsmentioning
confidence: 49%
“…In this paper, we examined the psychological health among children with TDBT and their mothers. We studied almost half of the TDBT patient population in Sri Lanka in the specified age group attending the three main thalassaemia centres of Sri Lanka which are situated in three different provinces of the country [9]. We found that children with TDBT in Sri Lanka have significantly higher prevalence of psychological symptoms in emotional, conduct and hyperactivity domains and abnormal peer relationships and social skills.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The same survey identified significant inconsistencies in care of SCD patients between centres. [11]. Genetic information including haplotype analysis for SCD in Sri Lanka is scarce, and has been reported for a single patient with SBT [12] only.…”
Section: Introductionmentioning
confidence: 99%
“…The same survey identi ed signi cant inconsistencies in care of SCD patients between centres. (11). Genetic information including haplotype analysis for SCD in Sri Lanka is scarce, and has been reported for a single patient with SBT (12) only.…”
Section: Introductionmentioning
confidence: 99%